2018
DOI: 10.24310/abm.v43i0.4966
|View full text |Cite
|
Sign up to set email alerts
|

Checklist of seaweeds of Al-Hoceima National Park of Morocco (Mediterranean Marine Protected Area)

Abstract: The Mediterranean basin is a marine biodiversity hot spot. Despite this, the macroalgal diversity of the Mediterranean Sea is still not fully known, especially in the Mediterranean Marine Protected Areas (MPAs) including, Al-Hoceima National Park of Morocco (PNAH). This paper provides the first comprehensive checklist of the seaweeds of PNAH, based chiefly on our own original collections, and complimented by literature records. Using present-day taxonomy, the total number of taxa at both specific and infraspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Seaweed production in Senegal was reported recently (Gueye et al 2020), with an estimated 80-100 t (FW) being exported to Japan. Moussa et al (2018), working in the Al-Hoceima National Park, reported 306 algal taxa including 207 red, 51 brown and 48 green seaweed and stated that amongst these were records of 10 new species. In a more recent study, Bahammou et al ( 2021) reported 156 species from 35 families of Rhodophyta.…”
Section: Senegalmentioning
confidence: 99%
“…Seaweed production in Senegal was reported recently (Gueye et al 2020), with an estimated 80-100 t (FW) being exported to Japan. Moussa et al (2018), working in the Al-Hoceima National Park, reported 306 algal taxa including 207 red, 51 brown and 48 green seaweed and stated that amongst these were records of 10 new species. In a more recent study, Bahammou et al ( 2021) reported 156 species from 35 families of Rhodophyta.…”
Section: Senegalmentioning
confidence: 99%
“…In the Pacific, it has been reported from Chile (Ramírez & Santelices, 1991), Hawaii (Abbott & Huisman, 2004) and Japan (Yoshida et al, 2015). In the Atlantic, it is known from the Azores Islands (Tittley & Neto, 1994), the Scandinavian Peninsula (Athanasiadis, 1996), the Bahamas (Ballantine & Aponte, 2003), Florida (Dawes & Mathieson, 2008), Brazil (Menezes-Széchy & Paula, 2010), Spain (Afonso-Carrillo, 2014), the Great Britain (Bunker et al, 2017), Morocco (Moussa et al, 2018) and France (Burel et al, 2019). Furthermore, the species has been found in the Mediterranean: in Egypt (Aleem, 1993), Libya and Tunisia (Ribera et al, 1992), Malta (Cormaci et al, 1997), Slovenia (Rindi & Battelli, 2005), Israel (Einav & Israel, 2008), (Taskin et al, 2008), Spain (Joher et al, 2012), Greece (Tsiamis et al, 2013), Algeria (Ould-Ahmed et al, 2013), Cyprus (Tsiamis et al, 2014) and Italy (Bottalico et al, 2016).…”
Section: Geographic Distributionmentioning
confidence: 99%